40.5k views
0 votes
2x + 4x = 3x + 3x Solve for x.

User Kalanidhi
by
4.7k points

1 Answer

4 votes

You have the following expression:

2x +4x = 3x + 3x

in order to solve for x, proceed as follow:

2x +4x = 3x + 3x simplify like terms both sides

6x = 6x

Due to the previous result is the trivial solution, it means that the equation has infinite solutions.

User Catalpa
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.